MITIGATING PERCEIVED IMPACTS OF ARTISANAL GOLD MINING PRACTICES ON AQUACULTURE, ENVIRONMENT AND LIVELIHOOD: POLICY OPTIONS FOR SUSTAINABLE FUTURE - Oyekanmi, Funmilayo Bosede; Adewale, Peter Sanjo; Ogunniyi, Gbadebo; Emefe, Oghenevwairhe; Oyekanmi, Oluwatomisin Adediji (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2025)
As Nigeria’s artisanal gold mining (AGM) sector continues to expand, the environmental and socio-economic costs of this practice are becoming increasingly evident. This study examines the impact of AGM activities on aquaculture and livelihoods among fisherfolks with a focus on policy options for a more sustainable future. Multistage sampling was used to select 120 fisherfolks as respondents for data collection. Questionnaire was used for data collection. The findings revealed significant environmental degradation, including land degradation, water pollution and loss of biodiversity which in turn affected the livelihoods of fisherfolks. Thus, the productivity of fishery activities is limited and livelihood is affected, thereby leading to a low standard of life among fishers. Additionally, there was a significant relationship between mining activities and the productivity of the aquaculture industry in Nigeria (r = 0.624, p = 0.001). This study recommends community-led initiatives for environmental conservation and socio-economic development.